1989
DOI: 10.1677/joe.0.1210253
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal mast cells modulate vascular and secretory responses in the intact adrenal gland of the rat

Abstract: Mast cells were identified in the rat adrenal gland, located in the walls of arterioles at the point at which they penetrate the connective tissue capsule. The mast cell products, histamine and serotonin, both caused dose-dependent increases in rates of perfusion medium flow and steroid secretion in the isolated, perfused rat adrenal gland in situ. Compound 48-80, a mast cell degranulator, caused a significant increase in perfusion medium flow rate and steroid secretion by the in-situ perfused rat adrenal. Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…It receives nearly 10-times the amount of blood flow as 20 expected from its organ size increasing its vulnerability for endothelial dysfunction and hemorrhage 21 In particular, it has been described that both angiotensin II and ACTH, the major regulators of adrenal 28 aldosterone and cortisol production, respectively, exert their function partially by enhancing the adrenal 29 blood flow. Previously, this stimulatory effect of adrenocorticotropin on adrenal vascular response was 30 found to be mediated via degranulation of mast cells (Hinson et al, 1989). More recently by using laser-31…”
Section: The Role Of Adrenal Gland Endothelial Cells In the Adrenal Dmentioning
confidence: 98%
“…It receives nearly 10-times the amount of blood flow as 20 expected from its organ size increasing its vulnerability for endothelial dysfunction and hemorrhage 21 In particular, it has been described that both angiotensin II and ACTH, the major regulators of adrenal 28 aldosterone and cortisol production, respectively, exert their function partially by enhancing the adrenal 29 blood flow. Previously, this stimulatory effect of adrenocorticotropin on adrenal vascular response was 30 found to be mediated via degranulation of mast cells (Hinson et al, 1989). More recently by using laser-31…”
Section: The Role Of Adrenal Gland Endothelial Cells In the Adrenal Dmentioning
confidence: 98%
“…This change in flow rate is believed to result from the interaction of ACTH and mast cells, located in the general capsular region near the afferent arterioles (Hinson et al, 1989). ACTH stimulation of the mast cells results in the local release of the vasoactive substances, histamine and serotonin (Hinson et al, 1986a), which have also been shown to increase the perfusion flow rate within the isolated perfused adrenal gland (Hinson et al, 1989). These vasoactive substances are thus believed to exert a direct vasodilatory effect upon the arteriolar component of the adrenal vasculature.…”
Section: Regulation Of Arterial Blood Flowmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] In the adrenal, exogenous 5-HT increases NA and adrenaline release and, thus, can affect the CV system by potentially increasing total peripheral resistance. …”
mentioning
confidence: 99%